Developing Patient-Centered Communication Models to Improve Patient Engagement and Enhance Clinical Efficiency - Tripathy, Debasmita; H, Malathi; Prakash Chandra, Pallavi (Seminars in Medical Writing and Education, 2023)
The importance of communication, centered around the patients, has proven effective in enhancing patient engagement and improving clinical efficiency despite restrictions of time and ability often preventing effective communication in circumstances surrounding trauma care. Breakdown of communication in such an environment shall bid a huge impact on the outcome of a patient; hence, that sets the background of developing a context within which communication strategies can happen to be responsive to the dynamics of the trauma team. Research recruited 126 medical hospital staff within trauma teams who had undergone communication training completely focused on patient-centered approaches. The training was to improve patient engagement and team communication during trauma encounters. Participants engaged in simulated trauma scenarios both before and after the training, which was followed by a 6-week follow-up. Data was analyzed with one way ANOVA with post-hoc Tukey’s test and regression analysis aimed at investigating the effect and sustainability of communication improvement. There was a significant improvement in communication and patient engagement behaviors after the training (p<0.05), and, although quite a renaissance regarding some loss of retention (p>0.05), those effects were maintained at the 6-week follow-up. Regression analysis showed that pre-training knowledge about communication and intensity of training for the retention of improved communication performance in the longer run were the two major factors. Research shows that brief training interventions can greatly improve trauma team communications for a long period of time, consequently leading to enhanced patient engagement as well as improved clinical efficiency.